Perceptional differences among small and marginal farmers on agricultural risks-a case study - Singh, Abhishek; Rajpoot, Kuldeep (Journal of Scientific Agriculture, 2025)
The study was carried out to find differences in the attitudes of the different categories of the farmers on different types of risks in order to assess their vulnerability to risks and their coping capacity to face risks. A survey was conducted in the Jabalpur district of the Indian state of Madhya Pradesh to ascertain the perceptions of the farmers to different types of risk involved in agriculture and an effort was made to determine whether these perceptions differ according to the land holding of the farmers. Results showed that there are differences in the coping capacity of the farmers based on their land holdings. This study will help the planners, government officials to have a relook at the management of risks for farmers by considering their land holding capacity as an important factor before implementation of any intervention. Of the many factors which affect the perceptions of farmers regarding risks in agriculture, the land holding of the farmer becomes a prominent one. New data has been generated and it modifies the existing theories regarding attitudes of farmers regarding risks.